Combustion and exhaust emission characteristics, and in-cylinder gas composition, of hydrogen enriched biogas mixtures in a diesel engine. (1st April 2017) - Talibi, Midhat; Hellier, Paul; Ladommatos, Nicos
Abstract: This paper presents a study undertaken on a naturally aspirated, direct injection diesel engine investigating the combustion and emission characteristics of CH4 -CO2 and CH4 -CO2 -H2 mixtures. These aspirated gas mixtures were pilot-ignited by diesel fuel, while the engine load was varied between 0 and 7 bar IMEP by only adjusting the flow rate of the aspirated mixtures. The in-cylinder gas composition was also investigated when combusting CH4 -CO2 and CH4 -CO2 -H2 mixtures at different engine loads, with in-cylinder samples collected using two different sampling arrangements. The results showed a longer ignition delay period and lower peak heat release rates when the proportion of CO2 was increased in the aspirated mixture. Exhaust CO2 emissions were observed to be higher for 60CH4 :40CO2 mixture, but lower for the 80CH4 :20CO2 mixture as compared to diesel fuel only combustion at all engine loads. Both exhaust and in-cylinder NOx levels were observed to decrease when the proportion of CO2 was increased; NOx levels increased when the proportion of H2 was increased in the aspirated mixture. In-cylinder NOx levels were observed to be higher in the region between the sprays as compared to within the spray core, attributable to higher gas temperatures reached, post ignition, in that region. Highlights: Hydrogen enriched biogas-diesel co-combustion was investigated. In-cylinder gas samples were collected from the chamber to gain further insight. 80CH4 :20CO2 mixture produced diesel-only combustion equivalent CO2 emissions. Inclusion of H2 in biogas mixtures significantly reduced particulate emissions. NOx levels were higher between diesel fuel sprays relative to within the spray.